Nonlinear interaction of intense laser beam with dense plasma. (25th November 2020) - Das, Chinmay; Chandra, Swarniv; Ghosh, Basudev
Abstract: We studied the nonlinear evolution of an amplitude-modulated envelop soliton formed in a dense plasma when a laser beam interacts with it. The employment of our newly developed technique, homotopy-assisted symbolic simulation, has been instrumental in the study of the nature and formation of envelope solitons and their dependence on various parameters. The different orders of homotopy perturbation generate a convergent series solution for such nonlinear coupled partial differential equations (PDE). Our technique bypasses the rigorous analytical derivation of coupled PDE without a loss of information. The methodology is very novel and holds promise for application in models that explain experimental observations. The results will be beneficial in interpreting various dense laser plasma interactions.